ffects of linguistic interference on the acquisition and transfer of conditional discriminations with first- and second-order matching-to-sample tasks - Alejandro León; Carlos Zenteno; Isiris Guzmán; Iván Felipe Medina-Arboleda (Acta Colombiana de Psicología, 2017)
Studies on conditional discrimination (CD) in humans have pointed out that linguistic contact with the properties and criteria of the task is critical both for acquisition and transfer, especially in extra-relational and extra-dimensional tests. Recentempirical and conceptual analyses have challenged this assumption. Studies in the field have generally included linguisticcomponents, but the effect of linguistic restriction through tasks that compete with verbal activity regarding tasks, such aslinguistic interference, has not yet been systematically explored. Two experiments were conducted: the first one used first-order matching-to-sample tasks (FOMST) and the second used second-order matching-to-sample tasks (SOMST), aiming to evaluate the effect of a linguistic interference task on the acquisition of conditional discrimination and functional adjustment in transfer tests (extra-instance, extra-modal, extra-relational, and extra-dimensional). Both experiments used an n = 1 design. A total of 24 college students participated, 12 in each study, and the effects of two experimental conditions were tested(Interference and No Interference, with six participants in each condition per study). The findings suggest that interference inlinguistic contact does not affect the acquisition of CD in FOMST or in SOMST, but it does affect the adjustment in transfer tests. In these, differential effects, by type, were observed in FOMST and SOMST.